Genetic engineering of Escherichia coli cells to increase production of Riboflavin. - Su, YanJie. (2013)
Riboflavin (Vitamin B2) is one of the essential vitamins required by humans and higher animals that can only be obtained by food consumption. Industrial production of riboflavin by biosynthetic pathway is needed to meet the demands of riboflavin as mostly feed additive and for fortification of food. Methods using genetic engineering are explored, in hope to find ways to reduce production cost and increasing the efficiency and yield of production. In this project, genetic engineering was employed onto Escherichia Coli cells by molecular cloning in hope to result in increased expression of 3, 4-Dihydroxy-2-butanone 4-phosphate (DHBP) synthase which in turn raise riboflavin production in cells. From the experiment carried out, recombinant plasmids that contained ribB gene are able to be transformed into Escherichia coli cells. The recombinant cells are also able to grow on culture hence proving that molecular cloning is successful